2007
DOI: 10.1111/j.1444-0938.2007.00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and blindness in Africa

Abstract: Africa carries a disproportionate responsibility in terms of blindness and visual impairment. With approximately 10 per cent of the world’s population, Africa has 19 per cent of the world’s blindness. It is no surprise that this reality also mirrors the situation in terms of the burden of world poverty. There is an increasing recognition of the need to highlight the link between poverty, development and health care. Blindness, disabling visual impairment and the overall lack of eye‐care services are too often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 28 publications
1
46
0
1
Order By: Relevance
“…Poverty is associated with cataract and blindness. 16 A study conducted in Pakistan showed that blindness was markedly more frequent in poor people. 17 The prevalence of blindness in low income countries is five times higher than their high income counterparts in a global level.…”
Section: Discussionmentioning
confidence: 98%
“…Poverty is associated with cataract and blindness. 16 A study conducted in Pakistan showed that blindness was markedly more frequent in poor people. 17 The prevalence of blindness in low income countries is five times higher than their high income counterparts in a global level.…”
Section: Discussionmentioning
confidence: 98%
“…Gleichzeitig sind die Ressourcen für eine rechtzeitige Behandlung der Patienten im Sinne einer Erhaltung des Augenlichts, die für die meisten zugrunde liegenden Erkrankungen -neben der diabetischen Retinopathie in erster Linie Katarakt, Trachom und Glaukom -technisch problemlos mçglich ist, im subsaharischen Afrika mit Ausnahme der Republik Südafrika vollkommen inadäquat [8,12]. Um die sehr ehrgeizigen Ziele des WHO-Programms "VISION 2020" für Afrika [21] auch nur ansatzweise zu verwirklichen, stünden eine wirksame Armutsbekämpfung und die Allokation substanzieller Ressourcen für die Behandlung der wichtigsten Augenkrankheiten durch die Regierungen der betroffenen Länder im Vordergrund [6,13]; realistisch ist dies bei allem Optimismus gegenwärtig nicht und die aktuelle politische Entwicklung in Kenia lässt eher eine Verschlechterung befürch-ten. Zwischen den WHO-Zielen und dem gegenwärtigen Status klafft aber eine derart große Lücke, dass auch unterhalb des "VISION 2020"-Programms ein erheblicher Raum für realistisch erzielbare Verbesserungen besteht.…”
Section: Materials Und Methodenunclassified
“…This gross inequity is mirrored in eye care, with sub-Saharan Africa bearing a huge burden of blindness (Naidoo et al 2014;Lewallen and Kello 2009) and acute shortages of eye care workers (Naidoo 2007) and yet, with its population of 936.1 million people (World Bank n.d.), only nine of the 48 countries have optometric education programmes (Oduntan et al 2014).…”
Section: Introductionmentioning
confidence: 99%